1998
DOI: 10.1007/bf02908725
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bacteria, phytoplankton and heterotrophic nanoflagellates along the trophic gradient

Abstract: Bacterial and heterotrophic ndnoflagellates (HNF) abundance, as well as bacterial production and chlorophyll a levels, were measured at live sites extending from the coastal zone toward the open Adriatic in the period from March to October "i995. The investigated areas were grouped into trophic categories according to concentrations of chlorophyll u. All the biotic-parrsmeters increased along the trophic gradient, ledding to eutrophy, but they did not increase at the same rate. The bacterial biomass : phytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
4
18
0
Order By: Relevance
“…Abundance of heterotrophic bacteria obtained by flow cytometry in the investigated coastal area and in the open Adriatic Sea area ranged from 10 5 to 10 6 cells mL -1 and results are similar to previous values obtained by epiflurescence microscopy reported for the eastern coast of Adriatic Sea (Krstulović et al, 1995;Krstulović et al, 1997). Seasonality in the bacterial community in the most investigated coastal areas ( Figure 5), with maxima in the spring-summer period and minima during winter was also determined, as in the previous reports on central Adriatic (Krstulović, 1992;Šolić et al, 2001).…”
Section: Resultssupporting
confidence: 89%
“…Abundance of heterotrophic bacteria obtained by flow cytometry in the investigated coastal area and in the open Adriatic Sea area ranged from 10 5 to 10 6 cells mL -1 and results are similar to previous values obtained by epiflurescence microscopy reported for the eastern coast of Adriatic Sea (Krstulović et al, 1995;Krstulović et al, 1997). Seasonality in the bacterial community in the most investigated coastal areas ( Figure 5), with maxima in the spring-summer period and minima during winter was also determined, as in the previous reports on central Adriatic (Krstulović, 1992;Šolić et al, 2001).…”
Section: Resultssupporting
confidence: 89%
“…Carvalho et al (2003) and Coveney and Wetzel (1995) also did not find a relationship between the chlorophyll and the bacterioplankton, during the studies carried out in oligotrophic and mesotrophic environments. The dependence of bacterioplankton of dissolved organic carbon released by the phytoplankton (Kisand et al, 2001) and the effect of the bacterivory in the control of the populations (Krstulovic et al, 1997) was more typical in the eutrophized environments (Gonzalez et al, 2000). Moreover, the low levels of chlorophyll denoted the importance of bacterioplankton for the trophic structuring of this environment, where significant relation between the bacteria and the phytoplankton was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Significant correlations between these biotic parameters suggest strong relationships in the microbial food web (Table 2). Earlier studies on the relationship between bacteria, phytoplankton and HNF in the eutrophicated part of Kaštela Bay showed that as much as 64% of variation in bacterial abundance could be explained either by variability in abundance of HNF or by predatorprey dependence (Krstulović et al, 1997). However, our data showed a slightly weaker link between bacteria and HNF abundance (r=0.40, N=36, P<0.05) and suggested that organisms other than HNF could be important predators of bacteria and/or that other loss processes could be more important than predation.…”
Section: Plankton Food Web Structurementioning
confidence: 99%